Blockchain-Enabled Supply Chain Optimization for Nepal’s Coffee Industry: A Data-Driven Forecasting and Efficiency Analysis - Khanal, Rishav (Journal of Engineering Issues and Solutions, 2025)
Coffee sector in Nepal comprises of 31,389 smallholder farmers who faces critical challenges in supply chain in inefficiencies like declining productivity and weak export performance. From 1999 to 2023, negative compound annual growth rate (CAGR) of -3.48% can be seen only with 19.6% of total production output being exported. This study foresees the historical trend analysis and predictive modeling including linear regression, moving average and Auto Regressive Integrated Moving Average (ARIMA) forecasting in order to explore the potential of blockchain technology addressing the systemic challenges. With the adoption of blockchain-enabled systems, this research forecasts that the integration with smart contract and Internet of Things (IoT) devices, Nepal’s coffee production could reach 540 metric tons annually by 2030, from 394 metric tons in 2023. This 25% improvement in productivity (from 107.8 kg/ha to 134.8 kg/ha) is supported by increased operational transparency, better resource coordination and reduced losses. Enhanced post-harvest management, driven by digital traceability will also help to project the lowering of wastage from 22.5% to 11%, boosting export volume by 30% to 127,660 kilograms per year. Implementation of blockchain is expects to command a 20% price premium in international market by ensuring authenticity and quality traceability, leading to estimated annual export revenue of NPR 229.8 million. The study outlines a phased implementation roadmap, demonstrating a return on investment (ROI) within just three months for pilot programs. Policy recommendations emphasize government-backed IoT subsidies and the formation of public-private partnerships to ensure broad-based adoption and long-term sustainability.